2013
DOI: 10.1002/jctb.4071
|View full text |Cite
|
Sign up to set email alerts
|

The sulfur chain in biogas production from sulfate‐rich liquid substrates: a review on dynamic modeling with vinasse as model substrate

Abstract: Vinasse is a sulfate-rich liquid substrate, from which high levels of hydrogen sulfide in biogas can be obtained due to the sulfate reduction process under anaerobic conditions. Hydrogen sulfide is corrosive and toxic and must be removed for any utilization of the biogas. Mathematical models have been developed to study separately sulfate reduction in anaerobic digestion and sulfide removal from biogas streams. However, the levels of hydrogen sulfide produced in the anaerobic digestion stage have an effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 43 publications
2
36
0
3
Order By: Relevance
“…Concerning the calibration of the sulfate reduction parameters, the yield coefficients, the Monod maximum specific uptake rates and the half saturation coefficients were found in the range of values found in the literature (Barrera et al, 2013). However, the 50% inhibitory concentrations of free H 2 S (Appendix A) were lower than the values used to calibrate the sulfate reduction processes (Barrera et al, 2013), but similar to experimental values reported as inhibitory (150 mg S L À1 (0.0047 kmol m À3 )) for methanogens and SRB (except for propionate degraders, which is 70 mg S L À1 (0.0022 kmol m À3 )) (Rinzema and Lettinga, 1988).…”
Section: Model Calibrationmentioning
confidence: 97%
See 2 more Smart Citations
“…Concerning the calibration of the sulfate reduction parameters, the yield coefficients, the Monod maximum specific uptake rates and the half saturation coefficients were found in the range of values found in the literature (Barrera et al, 2013). However, the 50% inhibitory concentrations of free H 2 S (Appendix A) were lower than the values used to calibrate the sulfate reduction processes (Barrera et al, 2013), but similar to experimental values reported as inhibitory (150 mg S L À1 (0.0047 kmol m À3 )) for methanogens and SRB (except for propionate degraders, which is 70 mg S L À1 (0.0022 kmol m À3 )) (Rinzema and Lettinga, 1988).…”
Section: Model Calibrationmentioning
confidence: 97%
“…The biological degradation processes are described using Monod kinetics, while the extracellular processes (disintegration and hydrolysis) and the biomass decay are described using firstorder kinetics. The ADM1 extension with sulfate reduction for high strength and sulfate rich wastewater was implemented in MatLab/Simulink 2008b following the original ADM1 (Batstone et al, 2002) and the approaches discussed by Barrera et al (2013). The model was implemented as a set of ordinary differential equations using the ODE 15s as numerical solver.…”
Section: Model Description and Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high sulfur composition of vinasse, AD produces a sulfur-rich biogas (Barrera et al, 2013), which could be highly corrosive to the burners by the production of SO2. Removal of SOx from biogas can be accomplished, among other technologies, through physical processes, such as sulfur-specific membrane filters, or through biological processes (Barrera et al, 2014).…”
Section: Ad Of Vinasse: Operation Energy Generation and Digestate Usementioning
confidence: 99%
“…The process generates solid and liquid residues, e.g., sugarcane bagasse and vinasse, respectively. Vinasse is also known as distillery wastewater, stillage, distillery spent wash and thin stillage; its main characteristics include a high chemical oxygen demand (COD), acidity (pH 3.5e5.5) and sulfate richness (2.1e15.8 kg m À3 ) [18,19]. Each liter of ethanol produced generates 13 L of vinasse [20].…”
Section: Introductionmentioning
confidence: 99%